FinTech : finance, technology, and regulation - Ross P. Buckley (Cambridge.: Cambridge University Press, 2024)
Examines how finance is being transformed by technology and innovation including AI, blockchain, BigData, cloud computing, cryptocurrencies, central bank digital currencies, and distributed ledger technology. Explores how societies can best benefit from, and how regulators and policymakers might best approach, the FinTech revolution